Analisis Faktor Eksternal dan Internal Bank terhadap Risiko Pembiayaan Bank Umum Syariah di Indonesia Periode 2012-2015 - Amalia Eka Purnamasari; Musdholifah Musdholifah (Universitas Negeri Surabaya, 2018)
The purpose of this research was to determine effect of growth gross domestic product, inflation, exchange rate, capital adequacy ratio, return on assets, operating expenses to operating revenues and bank size on financing risk (NPF) of Sharia Banks period 2012-2015. The data that use in this research is the secondary data, that is financial statement of Sharia Banks in Indonesia period 2012-2015. The sampling method that used in this research are purposive sampling and data analysis model used is the multiple linear regression analysis. The result of this research show that simultaneous each external and internal bank factor have influence on the NPF. But partially, showed that eksternal factor, namely growth gross domestic product, inflation and exchange rate have no influence on the NPF. While from the internal bank showed capital adequacy ratio and operating expenses to operating revenues have no influence, return on assets have a negative influence and bank size have a positive influence on the NPF.